(untitled) (Fiep Bulletin - online, 2014)
The objective of this study was to verify the influence of the force and flexibility in the beating of legs and its relation with the performance of 100m crawl style swimmers. The 23 best swimmers in the test of 100 meters crawl style (also known as freestyle) of the State of Rio Grande do Sul (Brazil) had been selected for this study and submitted to the evaluation of flexibility, capacity of force production, beating of legs and performance of crawl style in the distance of 100m. It had been analyzed the influence of the force and flexibility in the beating of legs, and the influence of the beating of legs in the swimmers total performance. After it, the sample was divided in three groups, as the time gotten in the test of beating of legs (group I: of 1º to 8º time; group II: of 9º to 16º time; e group III: of 17º to 23º time), with the objective to verify differences among the groups in the tested variables. The values gotten (n=23) from the correlation between plantar flexion and beating of legs had not been significant. In the sub-groups, only group "I" got significant correlation (r=0,70 - p<0,05) between plantar flexion and beating of legs. The values gotten from the force had not been correlated with the results gotten from the test of beating of legs, as much in the analysis of the whole group, as in the extracted groups. The times of beating of legs (n=23) had shown significant correlation (r=0,70 - p<0,05) with the total performance. The analysis made in the sub-groups only showed significant values for group "III" (r=0,85 - p<0,05), but did not show significant values for groups "I" and "II". The results suggested that the force does not have influence in the beating of legs, while flexibility influenced the beating of legs only in group "I", and that the total performance of swimmers of 100m crawl the beating of legs had indeed a significant importance in this study.